PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN VIDEO ANIMASI BERBASIS KEARIFAN LOKAL DI SEKOLAH DASAR - Hidayati, Aini; Fadhilaturrahmi, Fadhilaturrahmi; Mufarizuddin, Mufarizuddin; Aprinawati, Iis; Masrul, Masrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this research is the low mathematical communication skills of students in class V at SDN 007 Sipungguk. This research aims to improve students' mathematical communication skills using the Problem Based Learning (PBL) model assisted by animated videos based on local wisdom in class V at SDN 007 Sipungguk. This research is classroom action research carried out in two cycles and each cycle consists of 2 meetings. The subjects in this research were 20 class V students at SDN 007 Sipungguk, consisting of 12 male students and 8 female students. This research instrument consists of interview sheets, teacher activity observation sheets and student activity observation sheets, test sheets, and documentation sheets. Meanwhile, the data analysis techniques used are qualitative data analysis and quantitative data analysis. Based on the results of research that has been carried out in 2 cycles, in the first cycle of meeting 1 students who completed there were 10 students with a percentage of 50% with an overall average of 66 and at meeting 2 it rose to 13 students with a percentage of 65% with an overall average 67.25. Meanwhile, in cycle II, meeting 1, there were 16 students who completed it with a percentage of 80% with an overall average of 68.5, and there was an increase in meeting 2 to 18 students who completed it with a percentage of 90% with an overall average of 79.5. . Based on the results of this research, it shows that by implementing Problem Based Learning (PBL) learning assisted by animated video media based on local wisdom, it can improve the mathematical communication skills of class V students at SDN 007 Sipungguk.